Red Hamlet : the life and ideas of Alexander Bogdanov - White, James D., 1941- (Brill, 2018)
"In this first full-length biography of Alexander Bogdanov, James D. White traces the intellectual development of this key socialist thinker, situating his ideas in the context of the Russian revolutionary movement. He examines the part Bogdanov played in the origins of Bolshevism, his role in the revolutions of 1905 and 1917 and his conflict with Lenin, which lasted into Soviet times. The book examines in some detail Bogdanov's intellectual legacy, which, though deliberately obscured and distorted by his adversaries, was considerable and is of lasting significance. Bogdanov was an original and influential interpreter of Marx. He had a mastery of many spheres of knowledge, this expertise being employed in writing his chief theoretical work Tectology, which anticipates modern systems theory"-- Provided by publisher.
Keywords: Bogdanov, A. -- (Aleksandr), -- 1873-1928.; Bogdanov, A. -- (Aleksandr), -- 1873-1928; Revolutionaries -- Soviet Union -- Biography.; Communists -- Soviet Union -- Biography.; Russia -- History -- Revolution, 1905-1907.; Soviet Union -- History -- Revolution, 1917-1921.; Russie -- Histoire -- 1905-1907 (Révolution); URSS -- Histoire -- 1917-1921 (Révolution); BIOGRAPHY & AUTOBIOGRAPHY -- General.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Communists; Revolutionaries; Russia; Soviet Union; 1905-1921; Biographies; History